Electrochemical immunoplatform to unravel neurodegeneration and Alzheimer's disease through the determination of neurofilament light protein. (1st March 2021) - Valverde, A.; Montero-Calle, A.; Barderas, R.; Calero, M.; Yáñez-Sedeño, P.; Campuzano, S.; Pingarrón, J.M.
Highlights: Electrochemical immunoplatform for NfL determination. MBs-bearing sandwich immunocomplexes and amperometric detection at SPCEs. Unlike ELISAs, appropriate sensitivity (LOD of 3 pg mL-1) for plasma samples analysis. Accurate determination in plasma samples and brain tissues from non-demented control subjects and patients diagnosed with NDs. Simple and 1 h protocol requiring small sample amounts. Abstract: Alzheimer's disease (AD) is a common neurodegenerative disorder associated with massive degradation of neuronal cell structure due to aging. In recent years, neurofilament light chain (NfL) arises as one of the most promising blood biomarkers for AD. Bioassays available for NfL determination in blood (ELISA kits or Simoa assays) require multiple steps, specialized personnel and expensive instrumentation of application limited to centralized and high-resource environments. With the aim of overcoming these drawbacks, this work reports the first magnetic microbeads (MBs)-based electrochemical bioplatform developed so far for the determination of NfL. The developed platform relies in a sandwich type immunoassay involving an HRP-secondary antibody to enzymatically label the detector antibody on the surface of commercial MBs functionalized with carboxylic acids. Amperometric transduction is carried out at screen-printed carbon electrodes (SPCEs) upon deposition of the magnetic bioconjugates on the working electrode surface using the H2 O2 /hydroquinone (HQ) system. This MBs-based immunoplatform provides a LOD value of 3.0 pg mL −1 . The analytical performance is appropriate for the determination of NfL in plasma and brain tissues from AD patients using simple and short protocols (60 min) and requiring low amount of samples (5 µL raw plasma and 0.1 µg tissue extracts). Graphical abstract: Image, graphical abstract